Farmers' participatory seed production of IPB-bred varieties in relation to climate change adaptation - Narciso, Josefina O. (Journal of Environmental Science and Management, 2013)
The participation of farmers residing in agrarian reform communities towards the use of selected IPB-bred vegetable and peanut varieties was assessed. Purposive sampling of 18 pre-selected farmers was done and were trained on seed production and cultural management practices of these varieties at the Institute of Plant Breeding. After the implementation of seed production activities in their respective places, it was found that there was a dramatic increase in the amount of vegetable and peanut seeds produced in Antique, Samar, Davao del Sur and South Cotabato. The amount of seeds produced by farmer participants from Samar was highest at 96.2%. In contrast, the farmer participants from La Union produced the lowest amount of seeds. In relation to climate change adaptation, based from survey, the farmers will be considering a few adjustments in the future implementation of farming activities like adjustments to be made in the planting calendar of these varieties by the farmer participants due to heavy rains occurring starting September every year. Also, farmers will implement utilization of the legume residues for composting to produce organic fertilizers which was considered by all (100%) farmer participants. The peanut that can fix nitrogen from the air were also considered for crop rotation by majority (83.33%) of the farmers in order to lessen the use of inorganic fertilizers causing soil acidity. Further, the farmers indicated that peanut will be utilized for sequential cropping after rice to bring back soil fertility. All farmer participants from Antique, Samar, Davao del Sur and South Cotabato indicated the further adoption of the IPB-bred varieties in future production system. There was a highly significant association of the farmer participants' selected demographic variables with the amount of seeds produced.